City commercial banks and credit allocation: Firm-level evidence - Shulong Kang; Jianfeng Dong; Haiyue Yu; Jin Cao; Valeriya Dinger (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This paper investigates how government-led banking liberalization affects credit allocation by banks using as a quasi-natural experiment the establishment of city commercial banks (CCBs) in China. Based on more than three million corporate financial statements spanning over 16 years, we find that the establishment of CCBs led to a 6-14 % drop in debt funding for private firms, as well as a 1-2 % rise in their funding costs. At the same time, private infrastructure firms enjoyed a nearly 6 % increase in debt funding and more than 100-basis-point drop in interest costs despite their inferior credit quality. The debt financing of private firm appears most severely affected in municipalities where officials face high promotional pressures or fiscal constraints.
URN:NBN:fi:bof-202103091126
Keywords: D7; G21; G32; G38; P2; 330; banking liberalization; city commercial banks; bank lending; credit allocation; political economy in banking